2019
DOI: 10.7554/elife.49894
|View full text |Cite
|
Sign up to set email alerts
|

Human cytomegalovirus interactome analysis identifies degradation hubs, domain associations and viral protein functions

Abstract: Human cytomegalovirus (HCMV) extensively modulates host cells, downregulating >900 human proteins during viral replication and degrading ≥133 proteins shortly after infection. The mechanism of degradation of most host proteins remains unresolved, and the functions of many viral proteins are incompletely characterised. We performed a mass spectrometry-based interactome analysis of 169 tagged, stably-expressed canonical strain Merlin HCMV proteins, and two non-canonical HCMV proteins, in infected cells. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
102
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(117 citation statements)
references
References 86 publications
15
102
0
Order By: Relevance
“…ZAP-L is readily detectable in uninfected cells and its expression slightly increases throughout the first 48 hours of HCMV infection, while ZAP-S protein levels are low in uninfected cells and strongly upregulated from 6 hours post infection onwards. At a late stage of the HCMV life cycle, expression of both ZAP isoforms decreases, which likely reflects the fading type I IFN response rather than HCMV-mediated degradation (Nobre et al, 2019;Weekes et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…ZAP-L is readily detectable in uninfected cells and its expression slightly increases throughout the first 48 hours of HCMV infection, while ZAP-S protein levels are low in uninfected cells and strongly upregulated from 6 hours post infection onwards. At a late stage of the HCMV life cycle, expression of both ZAP isoforms decreases, which likely reflects the fading type I IFN response rather than HCMV-mediated degradation (Nobre et al, 2019;Weekes et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Another study has shown by siRNA-mediated knockdown that DDX3 acts as a proviral host factor during HCMV infection [34]. A recent mass spectrometry-based interactome analysis of all HCMV proteins did not identify DDX3 as a high-confidence interactor, but UBR5 was found to interact with six viral proteins, two of which are members of the US22 family: US26 and UL36 [56]. Moreover, another study demonstrated a role of PAIP2, whose stability is regulated by UBR5/EDD1, as a restriction factor limiting productive HCMV infection [33].…”
Section: Discussionmentioning
confidence: 99%
“…Proteins that interact with pp71 have been determined by multiple methods, including yeast two-hybrid screening, pulldown-mass spectrometry, and co-immunoprecipitation. Functions for most of the viral (Phillips and Bresnahan, 2011;Nobre et al, 2019) and cellular (Hofmann et al, 2002;Lee et al, 2012;Nobre et al, 2019) interactions are not known. The major interactors of pp71, for which functions have been established and are described below, include Daxx, STING, and the retinoblastoma (Rb) family of tumor suppressors.…”
Section: Pp71 Modifications Interactions Functions and Activitiesmentioning
confidence: 99%